Effect of pH-Responsive Charge-Conversional Polymer Coating to Cationic Reduced Graphene Oxide Nanostructures for Tumor Microenvironment-Targeted Drug Delivery Systems - Kitae Ryu; Jaehong Park; Tae-il Kim (Nanomaterials, 2019)
Tumor tissue represents a slightly acidic pH condition compared to normal tissue due to the accumulation of lactic acids via anaerobic metabolism. In this work, pH-responsive charge-conversional polymer (poly(ethylene imine)-poly(l-lysine)-poly(l-glutamic acid), PKE polymer) was employed for endowing charge-conversional property and serum stability to poly(ethylene imine) conjugated reduced graphene oxide-based drug delivery system (PEI-rGO). Zeta-potential value of PEI-rGO coated with PK5E7 polymer (PK5E7(PEI-rGO)) was −10.9 mV at pH 7.4 and converted to 29.2 mV at pH 6.0, showing pH-responsive charge-conversional property. Sharp-edged plate morphology of PEI-rGO was transformed to spherical nanostructures with vague edges by PK5E7 coating. Size of PK5E7(PEI-rGO) was found to be smaller than that of PEI-rGO in the serum condition, showing its increased serum stability. Loaded doxorubicin (DOX) in PK5E7(PEI-rGO) could be released rapidly in lysosomal condition (pH 5.0, 5 mM glutathione). Furthermore, DOX-loaded PK5E7(PEI-rGO) showed enhanced anticancer activity in HeLa and A549 cells in the tumor microenvironment-mimicking condition (pH 6.0, serum), which would be mediated by non-specific cellular interaction with decorated serum proteins. These results indicate that the pH-responsive charge-conversional PKE polymer coating strategy of cationic rGO nanostructures possesses a potential for acidic tumor microenvironment-targeted drug delivery systems.